Fear of Missing Out and Cryptocurrency Investment Awareness and Readiness Among Generation Z: a Mixed Methods Study - Azzaitun Nur Rachma; Laila Listiana Ulya (Universitas Ahmad Dahlan, 2026)
This explanatory sequential mixed-methods study examined whether fear of missing out (FOMO) predicts cryptocurrency investment awareness and readiness among Generation Z and explored how this psychological process is experienced in investment decision-making. The quantitative phase involved 150 participants, followed by a qualitative phase consisting of one focus group discussion with eight participants and two in-depth interviews to explain and contextualize the statistical findings. Confirmatory factor analysis generally supported the measurement models, although the social FOMO subscale showed limited reliability and was therefore interpreted cautiously. More than half of the participants (56.00%) reported high or very high levels of FOMO. After controlling for gender, age, income, investment experience, and investment frequency, FOMO remained a significant positive predictor of investment awareness and readiness, although its incremental contribution was small. Exploratory descriptive findings suggested that social FOMO may be more salient than personal FOMO; however, this pattern should be considered tentative due to the limited reliability of the subscale. Thematic analysis generated six interconnected themes concerning the formation of FOMO, its behavioral manifestations, perceived consequences, turning points, self-regulation strategies, and investment readiness. The qualitative findings suggested that FOMO operates not merely as a stable dispositional tendency but as a dynamic psychological process shaped by peer comparison, digital exposure, emotional arousal, and experiential learning. These findings extend behavioral finance literature by positioning FOMO as both a risk-related psychological driver and a potentially modifiable process in cryptocurrency investment readiness. Practically, the study highlights the need for psychologically informed financial education that integrates crypto-literacy, emotional regulation, risk reflection, and critical investment decision-making among young investors.